2023
DOI: 10.1111/tid.14032
|View full text |Cite
|
Sign up to set email alerts
|

Utility of deceased donor cultures in solid organ transplantation in preventing donor‐derived bacterial and fungal infectious diseases transmission

Abstract: Deceased donor and organ perfusion fluid cultures are obtained in order to inform recipient antimicrobial management and therefore reduce the risk of donor‐derived bacterial and fungal infections. However, important heterogeneity exists in laboratory practice across organ procurement organizations and clinical management of culture results across transplant centers. While not standardized, the clinical approach to donors with positive bacterial and/or fungal cultures should be informed by the risk of donor‐der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Donor-derived infections can be categorized into two groups: “expected” and “unexpected.” Expected transmission events occur when a known infection is identified in a potential donor, with the recognized potential for transmission to one or more recipients. The most common infections in this category are viral pathogens such as cytomegalovirus (CMV), Epstein-Barr virus (EBV), and hepatitis B and C. Bacterial, fungal, and parasitic transmissions can also occur as the result of infection or colonization of the donor organ, contamination during organ recovery, or transmission through the bloodstream during the transplantation process ( 5 ). Preventative strategies such as targeted antimicrobial prophylaxis, perioperative infection prevention measures, and post-transplant surveillance can minimize the risk and impact of expected disease transmission.…”
Section: Expected Transmission Eventsmentioning
confidence: 99%
“…Donor-derived infections can be categorized into two groups: “expected” and “unexpected.” Expected transmission events occur when a known infection is identified in a potential donor, with the recognized potential for transmission to one or more recipients. The most common infections in this category are viral pathogens such as cytomegalovirus (CMV), Epstein-Barr virus (EBV), and hepatitis B and C. Bacterial, fungal, and parasitic transmissions can also occur as the result of infection or colonization of the donor organ, contamination during organ recovery, or transmission through the bloodstream during the transplantation process ( 5 ). Preventative strategies such as targeted antimicrobial prophylaxis, perioperative infection prevention measures, and post-transplant surveillance can minimize the risk and impact of expected disease transmission.…”
Section: Expected Transmission Eventsmentioning
confidence: 99%
“…3,8,9 Infections outside of target organs have a low risk of transmission and may be overlooked. 9 Solid organ transplantation from donors with isolated bacteremia may similarly be safe, although evidence is limited for lung transplantation. [10][11][12] Shah et al published the largest report of lung transplant donors with bacteremia and found no adverse effect on recipient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines recommend obtaining cultures from donor allografts and blood, as infections at these sites may increase the risk of invasive infections after transplantation and may adversely affect graft function 3,8,9 . Infections outside of target organs have a low risk of transmission and may be overlooked 9 . Solid organ transplantation from donors with isolated bacteremia may similarly be safe, although evidence is limited for lung transplantation 10–12 .…”
Section: Introductionmentioning
confidence: 99%